Phylogeny, Antifungal Susceptibility, and Point Mutations of SQLE Gene in Major Pathogenic Dermatophytes Isolated From Clinical Dermatophytosis - Pashootan, Nasrin; Shams-Ghahfarokhi, Masoomeh; Chaichi Nusrati, Arash; Salehi, Zahra; Asmar, Mehdi; Razzaghi-Abyaneh, Mehdi (Frontiers in Cellular and Infection Microbiology, 2022)
Drug resistance is one of the major challenges to skin fungal infections, especially in tropical and subtropical infections caused by dermatophytes. This study aimed to determine the antifungal susceptibility of clinically dermatophytes and evaluate point mutations in terbinafine-resistant isolates. A total number of 123 clinical dermatophyte isolates in eight species were evaluated in terms of sensitivity to seven major antifungals. Furthermore, the point mutation in squalene epoxidase (SQLE) gene responsible for terbinafine resistance was studied. The dermatophytes species were identified by morphological characteristics and confirmed by the ITS sequencing. Also, the phylogenetic tree was drawn using the RAxML analyses for 123 dermatophytes isolates. A new XXIX genotype was also found in 4 Trichophyton mentagrophytes isolates. Based on the results obtained, terbinafine was the most effective antifungal drug followed by itraconazole and voriconazole. Trichophyton rubrum and Trichophyton tonsurans were the most susceptible species (MIC50 = 0.01, 0.09 μg/ml), and T. mentagrophytes was the most resistant species (MIC50 = 0.125 μg/ml) to terbinafine. Of the 123 dermatophytes isolates, six isolates showed reduced susceptibility to terbinafine, and only Trichophyton indotineae had a mutation in SQLE gene as a Phe397Leu substitution. Overall, the antifungal susceptibility test is necessary for managing dermatophytosis. These results help physicians to control the course of the disease and provide further insights to select effective drugs for patients with dermatophytosis, especially in tropical and subtropical regions of the world, where dermatophytosis is still a public health problem.